Quality of Life in Arthritis Patients Using Nonsteroidal Anti-Inflammatory Drugs. (1st May 1999) - Wiklund, Ingela
Abstract : Arthritis is a painful and disabling condition. To suppress the pain and the inflammatory process, patients are often chronic nonsteroidal anti-inflammatory drug (NSAID) users. Chronic use of NSAIDs may induce peptic ulcer, dyspeptic problems and heartburn. Therefore, these patients are often provided with treatment to relieve and/or protect against gastrointestinal problems. Rheumatic disorders also affect a range of health-related quality of life domains. In one study, patients with NSAID-associated gastroduodenal lesions complained about lack of energy, sleep disturbances, emotional distress and social isolation in addition to pain and mobility limitations. The degree of distress and dysfunction differed markedly from scores in an unselected population. Clinical trial data suggest that acid-suppressing therapy with omeprazole is superior to therapy with misoprostol and ranitidine in healing gastroduodenal lesions and preventing abdominal pain, heartburn and indigestion symptoms during continued NSAID treatment. Because arthritic patients are severely incapacitated by their condition regarding most aspects of health-related quality of life, it is important to offer a treatment that is effective in healing and preventing NSAID-induced ulcers and gastrointestinal symptoms during continued NSAID treatment without further compromising the patients' quality of life. Treatment with omeprazole once daily has been shown to be superior to that with ranitidine and misoprostol in this respect.